2022
DOI: 10.1111/jfpe.14034
|View full text |Cite
|
Sign up to set email alerts
|

Mass detection of walnut based on X‐ray imaging technology

Abstract: In view of the problem of low accuracy in walnut mass detection caused by relatively inconstant density, this study suggested the integration of X‐ray imaging technology and image processing technology with machine learning for walnut mass detection. Using image processing technology to remove the background of walnut X‐ray image and to segment the kernels, the mass prediction models could be constructed after extracting the shape and texture of walnut characteristic parameters and the kernel shape characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In particular, they observe that larger fruits are correlated with rougher shell shape and smaller kernel filling ratio, which allows them to select for better genotypes. X-ray CT imaging has also been recently used to document morphological changes of walnut flower bud development (Gao, 2022), estimate kernel weight in an nondestructive way (Gao et al, 2022), and to explore the puzzling diversity and structure of the cell tesselations that conform the hard shell tissue for multiple nuts (Huss et al, 2020).…”
Section: Core Ideasmentioning
confidence: 99%
“…In particular, they observe that larger fruits are correlated with rougher shell shape and smaller kernel filling ratio, which allows them to select for better genotypes. X-ray CT imaging has also been recently used to document morphological changes of walnut flower bud development (Gao, 2022), estimate kernel weight in an nondestructive way (Gao et al, 2022), and to explore the puzzling diversity and structure of the cell tesselations that conform the hard shell tissue for multiple nuts (Huss et al, 2020).…”
Section: Core Ideasmentioning
confidence: 99%
“…Therefore, it is necessary to develop a non-destructive and rapid method for identifying maize seed varieties. Near-infrared spectroscopy and machine vision technologies have been widely applied in the field of agricultural product inspection ( Gao et al, 2020 ). Near-infrared spectroscopy can more accurately detect the internal composition of a sample, such as protein and moisture ( Serrano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After picking, internal defects, such as protein deterioration, flavor loss, shriveled seed kernel, and empty shell, and external mechanical damage in walnuts can occur during transportation, processing, and storage [2]. These seriously reduced the grade and commodity rate of walnuts and greatly weakened their market competitiveness [3]. At present, the detection methods used to identify the internal quality of walnuts are manual detection, physical means, or stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Van et al [13] and Tim et al [14] reported the internal-defects detection of apples and 'Conference' pears, achieving accuracy rates of 90% and 90.2%, respectively. Gao et al [15] and Zhang et al [16] also successfully applied it to detect whether hard-shelled walnuts had become hollow and also to detect the size of the walnut kernel. Such X-ray image technology has led to promising results in real-time, non-destructive testing of internal defects in intact walnuts with shells.…”
Section: Introductionmentioning
confidence: 99%